Peranan penyesuaian diri di perguruan tinggi terhadap stres akademik pada mahasiswa perantau di Jakarta - Saniskoro, Bia Sabrina Rahayu; Akmal, Sari Zakiah (Konsorsium Psikologi Ilmiah Nusantara, 2017)
Many qualified educational institution in Jakarta became one of the factors that make students decide to study in Jakarta. The migrant students experience different situation from non-migrant students, they are required to be able to adapt themselves to the academic transition and other issues like social environment in their new region. The failure of migrant students in adjusting themselves in university and their neighborhood can cause negative effects, such as academic stress. This study aims to determine the role of college adjustment on academic stress, by involving 310 migrant students in Jakarta. This study employed the Student Adaptation to College Questionnaire (SACQ) and Educational Stress Scale for Adolescents (ESSA). The results of multiple regression test showed that there was 17.9% of role of collage to adjustment on academic stress. The dimensions that contribute to academic stress include personal-emotion adjustment and institutional attachment.